Rain forest - Hughes, Carol; Hughes, David; Kane, Dennis B.; Skinner, Thomas; National Geographic Society; WQED (Television station : Pittsburg, Pa.). (Washington, D.C. The Society, 1983)
Showcases the rare beauty and rich variety of plant and animal life found in a Costa Rican rain forest. Also examines the impact of man's exploitation of the rain forest on this fragile ecosystem.
VHS.
Narrated by Richard Kiley ; edited by Barry Nye.
Keywords: Rain forest ecology -- Costa Rica; Ecology; Nature -- Effect of human being on -- Costa Rica